2006
DOI: 10.1051/parasite/2006131035
|View full text |Cite
|
Sign up to set email alerts
|

Programme africain de lutte contre l’onchocercose (APOC) : transmission d’Onchocerca volvulusparSimulium damnosumS. l. dans deux régions de la République Centrafricaine

Abstract: Summary : AFRICAN PROGRAMME FOR ONCHOCERCIASIS CONTROL (APOC): ONCHOCERCA VOLVULUS TRANSMISSION BY SIMULIUM DAMNOSUM S. L. IN TWO REGIONS OF THE CENTRAL AFRICAN REPUBLICEntomological baseline data were collected in the villages of Zinga and Boali-Falls in Central African Republic (CAR) in view of the long term impact assessment of community-directed treatment with ivermectin (CDTI). Morphological determinations revealed that flies caught in both sites belong to the sub-group Sou/Sq. In Boali, the nuisance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
3
1
1
1
Order By: Relevance
“…This may also explain the relatively high mf prevalence obtained in most of the communities surveyed globally. The same trend was seen while comparing our entomological data in Bolo with that collected in 1998 and 1999 [ 37 ]. Moreover, in Bakumba we noted that the pre-control infective rate was lower than the infective rate observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…This may also explain the relatively high mf prevalence obtained in most of the communities surveyed globally. The same trend was seen while comparing our entomological data in Bolo with that collected in 1998 and 1999 [ 37 ]. Moreover, in Bakumba we noted that the pre-control infective rate was lower than the infective rate observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Our results corroborate with those of Nascimento-Carvalho in Brazil or Homoxi, where the biting activity of female Simuliidae showed a bimodal pattern, with peaks in activities early morning (between 7 and 8.50 a.m.) and afternoon (between 4 and 5.50 p.m.) [39]. In Thirei, the biting activity was evenly distributed throughout the day [40]. Black ies were captured simultaneously in Homoxi and Thirei using systematic methods to compare the traditional capture method using human bait (Human Landing Catch, HLC) with HLC protected by MosqTent® [39].…”
Section: Entomological Parameterssupporting
confidence: 91%
“…The black y survival rate, in our study, was not as low as that reported by Makenga et al (2015) [27]. Contrarily, observed a relatively higher percentage at Zinga in the Central African Republic, with an estimated parity rate of 5.3% [40], than Kahn, Cameroon (parity rate: 7.2%) [22]. The higher parity rate in the Cameroonian study was because it was conducted for 12 months.…”
Section: Entomological Parameterscontrasting
confidence: 59%
See 1 more Smart Citation
“…Les simulies sont dites infectées lorsqu'elles hebergent des larves évolutives (L1, L2 ou L3), quelle que soit leur localisation. Les simulies hébergeant des larves infectantes dans la tête sont appelées simulies infectieuses (Enyong et al, 2005). Toutes les observations sont transcrites sur une fiche de dissection journalière qui est jointe à la fiche de capture.…”
Section: Capture Des Femelles De Simulies Et Dissectionunclassified